Aristolochic Acid-Induced Autophagy Promotes Epithelial-to-Myofibroblast Transition in Human Renal Proximal Tubule Epithelial Cells. (18th October 2017) - Man, Yu-Lin; Rui, Hong-Liang; Chen, Yi-Pu; Wang, Guo-qin; Sun, Li-Jun; Cheng, Hong
Abstract : Autophagy plays an essential role in cellular homeostasis in kidney. Previous studies have found that aristolochic acid (AA) can induce autophagy of renal tubular epithelial cells and epithelial-to-myofibroblast transition (EMT). However, the relationship between AA-induced autophagy and EMT is unclear. Our results showed that, after AA stimulation, the appearance of autophagy preceded EMT. Autophagy of HKC cells began to increase gradually from the 3rd hour, reached the peak at 12th hour, and then weakened gradually until 36th hour; the EMT process of HKC continued to increase from 6th hour to 36th hour after AA stimulation. The enhancement of autophagy using autophagy inducers, rapamycin or serum-free medium, led to an aggravation of EMT and upregulated expression of fibronectin, a component of extracellular matrix, in AA-treated HKC cells. In contrast, the inhibition of autophagy by autophagy inhibitor, 3-methyladenine, or by knockdown of Beclin 1 led to an attenuation of EMT and downregulated expression of fibronectin in AA-treated HKC cells. Taken together, our study suggests that, after AA stimulation, two types of cell responses of HKC cells, autophagy and EMT, will successively appear, and autophagy can promote EMT of HKC.